Typology of teacher development - Viktory Nicodemus Joufree Rotty; Lady Grace Jane Giroth; Kyrie Eleison Ruata; Tiersa Reinie Undap; Anita Costanci Christine Tengker (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
The teacher resources development becomes a central issue in public discussion. The plan, implementation, monitoring and evaluation of teacher resource development in Dinas Pendidikan Manado is being provoked and receives attention. The provoking issues play around on how teacher resouces development being planned, implemented, and evaluated. This study takes a qualitative approach and utilizes a case study method. In-depth interviews are the primary data collecting tools, followed by document study techniques/literature and observation. However, monitoring and evaluation success requires adequate implementation quality, appropriate monitoring and evaluation standards, and a special monitoring and evaluation budget. In conclusion, the government should inform and promote the pattern of execution of teacher resource development. That is, more attention and a dedicated budget for the creation of teaching resources are required. The pattern of teacher resource development monitoring and assessment is based on both internal and external stakeholders. The government must state and report the pattern of implementation of teacher resource development. This means that more attention and special budget are needed to create teaching resources. The pattern of monitoring and assessment of teacher resource development is based on internal and external interests. As a result, by using explicit and redundant standards, supervisor quality becomes an important predictor of successful monitoring and assessment.